Omani Educational Supervisors’ Perceptions of 7th and 8th grades’ Cambridge Mathematics Curriculum in Light of Knowledge-based Economy and its Relationship with Their Attitudes Towards The Curriculum - Al-harusi, Issa Khamis Ali; Bin Ibrahim, Mohd Burhan; Al-daba, Abdulmajid Mohammed (Journal of Educational and Psychological Sciences, 2021)
The purpose of the current study was to identify the level of Omani educational supervisors’ perceptions of the 7th and 8th grades’ Cambridge mathematics curriculum in light of the knowledge-based economy and their attitudes towards the curriculum. It also aimed to examine the causal relationship between their perceptions of and their attitudes towards the curriculum. To achieve these objectives, the study conducted a 30 items cross-sectional survey (questionnaire) among 72 mathematics supervisors in Sultanate of Oman. Descriptive statistics i.e., means and standard deviations were used to identify the level of the educational supervisors’ perceptions and attitudes, while inferential analyses i.e., simple linear regression was employed to examine the causal relationship between the two variables. The results of this study showed high level of perceptions among the educational supervisors about the 7th and 8th grades’ Cambridge mathematics curriculum in light of the knowledge-based economy (Mean= 3.62). The results also showed a high attitude towards the curriculum (Mean= 3.95). Moreover, the results revealed a statistically significant relationship between the educational supervisors’ perceptions and their attitudes towards the curriculum.